Encyclopedia of Public Health - Kirch, Wilhelm; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
The Encyclopedia of Public Health presents the most important definitions, principles and general perspectives of public health, written by experts of the different fields. The work includes more than 2,500 entries in alphabetical order. Entries comprise review-style articles (synopses), detailed essays and short definitions. Extensive cross referencing and hyperlinking offers an easy to use web of knowledge in Public Health. Solidly structured and inclusive, this two-volume reference is an invaluable tool for clinical scientists and practitioners in academia, health care and industry, as well as students and teachers.
Keywords: Medicine; Public health; Medicine & Public Health; Public Health; Medicine/Public Health, general; Electronic books